2019
DOI: 10.1089/wound.2017.0781
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Activity of Plants from the Convolvulaceae Family

Abstract: Significance: Compounds derived from plants are gaining importance for the treatment of several diseases. Many plants from the Convolvulaceae family contain compounds that have demonstrated wound healing and antidiabetic activity. Such compounds can be effectively used as a part of treatments to promote wound healing in diabetics and used in combination with antimicrobial therapy to reduce the likelihood of drug resistance and allergic reactions. Novel strategies for developing herbal formulations such as nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…They indicated that such extract possesses anti-inflammatory and wound healing activity which may justify its medicinal uses in the treatment of wounds. The PAL formulated cream at several concentrations of 1.25, 2.5, 5 and 10% w/v verified wound healing properties with obvious angiogenesis, collagenation and re-epithelization distinctive of fibrous tissue formation in wound bed [12] as presented in Figure 2.…”
Section: Introductionmentioning
confidence: 74%
“…They indicated that such extract possesses anti-inflammatory and wound healing activity which may justify its medicinal uses in the treatment of wounds. The PAL formulated cream at several concentrations of 1.25, 2.5, 5 and 10% w/v verified wound healing properties with obvious angiogenesis, collagenation and re-epithelization distinctive of fibrous tissue formation in wound bed [12] as presented in Figure 2.…”
Section: Introductionmentioning
confidence: 74%
“…The prevailing compounds of ethanolic extract of Pleurotus eryngii which have been reported to possess pharmacological potentials viz. antiobesity, antimicrobial, antihyperglycemic, antioxidant, anti-inflammatory and anticarcinogenic in the literature are conhydrin, diethyl phthalate, and phthalic acid-butyl hex-3-yl ester (alkaloids) [26] , ar-turmerone (sesquiterpenoid) [27] , palmitic acid, myristic acid, phenol, and benzoic acid [28] . Namba et al demonstrated that water extract of Pleurotus eryngii reduces pancreatic lipids [29] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tubers also contain high amounts of minerals likes zinc, potassium, sodium, manganese, calcium, magnesium, and iron. They are also rich in carbohydrates and fibre [6].…”
Section: Introductionmentioning
confidence: 99%